2012
DOI: 10.1021/ja2108799
|View full text |Cite
|
Sign up to set email alerts
|

Tin Oxide Dependence of the CO2 Reduction Efficiency on Tin Electrodes and Enhanced Activity for Tin/Tin Oxide Thin-Film Catalysts

Abstract: The importance of tin oxide (SnO(x)) to the efficiency of CO(2) reduction on Sn was evaluated by comparing the activity of Sn electrodes that had been subjected to different pre-electrolysis treatments. In aqueous NaHCO(3) solution saturated with CO(2), a Sn electrode with a native SnO(x) layer exhibited potential-dependent CO(2) reduction activity consistent with previously reported activity. In contrast, an electrode etched to expose fresh Sn(0) surface exhibited higher overall current densities but almost e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

54
824
2
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 921 publications
(891 citation statements)
references
References 29 publications
54
824
2
11
Order By: Relevance
“…36). However, for np-Ag, the Tafel slope of 58 mV dec À 1 indicates a fast initial electron transfer step before a later non-electron transfer rate-determining step 15,36,37 , which proves that the np-Ag surfaces are able to stabilize the CO 2 À intermediate much better than a flat surface. Therefore, the dramatic decrease in Tafel slope for np-Ag indicates that, in addition to 150 times larger electrochemical surface area, np-Ag is also intrinsically better than polycrystalline Ag for CO 2 reduction at moderate overpotentials.…”
Section: Discussionmentioning
confidence: 94%
“…36). However, for np-Ag, the Tafel slope of 58 mV dec À 1 indicates a fast initial electron transfer step before a later non-electron transfer rate-determining step 15,36,37 , which proves that the np-Ag surfaces are able to stabilize the CO 2 À intermediate much better than a flat surface. Therefore, the dramatic decrease in Tafel slope for np-Ag indicates that, in addition to 150 times larger electrochemical surface area, np-Ag is also intrinsically better than polycrystalline Ag for CO 2 reduction at moderate overpotentials.…”
Section: Discussionmentioning
confidence: 94%
“…57 There has also been substantial interest in high surface area Cu-based catalysts for CO 2 reduction, and in particular those derived from the reduction of oxidized Cu. 4,7,[58][59][60][61][62][63][64] It has been reported that pre-oxidized Cu catalysts exhibit an exceptionally high activity for producing multi-carbon products, such as C 2 H 4 and C 2 H 5 OH. These studies have stimulated efforts aimed at understanding the origin of the seemingly superior catalytic activity of these oxide-derived catalysts compared to polycrystalline Cu foils.…”
Section: ‫ܣܥܵܧ‬ = ‫ܥ‬ ‫ܥ‬ ோாிmentioning
confidence: 99%
“…18 Rosenthal and co-workers have reported a generalized strategy for the electrodeposition of inexpensive electrocatalytic films from triflate salts of Bi 3+ , Sb 3+ , Sn 2+ , and Pb 2+ in organic media. [19][20][21] When the Bi-based electrodes are used for electrochemical CO 2 reduction in acetonitrile with a low overpotential of 250 mV, the 4 electrocatalysts are highly selective towards CO only when an appropriate ionic liquid is present in the system (1-ethyl-3-methylimidazolium hexafluorophosphate [EMIM]PF 6 , or 1-butyl-3-methylimidazolium hexafluorophosphate [BMIM]PF 6 , with an average 81% CO FE with [25][26][27][28][29][30] mA cm −2 ). [19][20][21] These seminal studies have thus clearly indicated that non-noble catalysts have the capability to compete with noble metals for CO 2 reduction.…”
mentioning
confidence: 99%
“…25 In contrast, oxidized Sn dendrites exhibited ~30 to 50% FE towards formate at −0.66 V vs. RHE, together with 20% FE to CO. 28 Electrodeposited SnO x thin films on an Sn sheet substrate produced formate with a 40% FE yet with an increased selectivity towards CO (60% FE at −0.7 5 V vs. RHE). 29 This increased selectivity, compared with pristine Sn, was ascribed to the surface oxide species, which may stabilize the CO 2 − intermediate. 28,29 Consistently, H 2 was favored when more positive potentials than −0.7 V vs. RHE were applied to the Sn surface but with lower current densities due to the high overpotential to catalyze the hydrogen evolution reaction on metallic Sn.…”
mentioning
confidence: 99%